Differential Invariants of Conformal and Projective Surfaces - Hubert, E.; Olver, P.J. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We show that, for both the conformal and projective groups, all the differential invariants of a generic surface in three-dimensional space can be written as combinations of the invariant derivatives of a single differential invariant. The proof is based on the equivariant method of moving frames.